2010
DOI: 10.1590/s1516-18462010005000133
|View full text |Cite
|
Sign up to set email alerts
|

Inclinação de cabeça durante a mastigação habitual nas deformidades dentofaciais classe II e III

Abstract: OBJETIVO: este estudo investiga a diferença entre grupos com deformidade dentofacial (padrão classe II e classe III), em relação à preferência mastigatória referida e inclinação de cabeça durante a mastigação, assim como predomínio intra-grupo de cada um desses aspectos, comparativamente a um grupo controle. MÉTODOS: participaram deste estudo, voluntariamente, 25 pacientes (entre 18 e 35 anos). Doze pacientes com diagnóstico de deformidade dentofacial classe II e 13 pacientes com o diagnóstico de classe III es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…What happens is that during surgery there may be trauma of the Inferior Alveolar Nerve, thus causing abnormal sensitivity in the region of ment, inferior lip and injured side of cheek 5,7,20,21 . The chewing pattern found suggests the presence of alteration in this role due to dentofacial deformity, being common the preference for one chewing side 22 and reduction of the chewing efficiency 23 . Furthermore, it was observed that the number of chewing strokes and time spent in the function is not uniform 24 , being greater in the postoperative evaluation at 90 days.…”
Section: Resultsmentioning
confidence: 94%
“…What happens is that during surgery there may be trauma of the Inferior Alveolar Nerve, thus causing abnormal sensitivity in the region of ment, inferior lip and injured side of cheek 5,7,20,21 . The chewing pattern found suggests the presence of alteration in this role due to dentofacial deformity, being common the preference for one chewing side 22 and reduction of the chewing efficiency 23 . Furthermore, it was observed that the number of chewing strokes and time spent in the function is not uniform 24 , being greater in the postoperative evaluation at 90 days.…”
Section: Resultsmentioning
confidence: 94%
“…Although some studies have shown that healthy individuals may present a unilateral predominance, the chewing normal physiology is characterized by unilateral cycles with periodic alternation of food on the two sides of the dental arch 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Além da preferência mastigatória unilateral, indivíduos com deformidades dentofaciais também podem apresentar maior predomínio de inclinação de cabeça durante a mastigação (DEDA et al, 2011); porém, esse aspecto não foi avaliado no presente estudo. A literatura também já ponderou que a preferência mastigatória pode ser relacionada a um controle central, e às lateralidades hemisféricas (de mãos, pés, olhos e orelhas), descartando-se a correlação com a oclusão, gênero, guias oclusais e as perdas dentárias (NISSAN et al, 2004).…”
Section: Análises Dos Dadosunclassified